Symbiotic and toxinogenic Rhizopus spp. isolated from soils of different papaya producing regions in Mexico - Cabrera-Rangel, José Francisco; Mendoza-Servín, Judit Valeria; Córdova-López, Gonzalo; Alcalde-Vázquez, Raúl; García-Estrada, Raymundo Saúl; Winkler, Robert; Partida-Martínez, Laila P. (Frontiers in Fungal Biology, 2022)
Mucoralean fungi from the genus Rhizopus are common inhabitants of terrestrial ecosystems, being some pathogens of animals and plants. In this study, we analyzed the symbiotic and toxinogenic potential of Rhizopus species derived from agricultural soils dedicated to the production of papaya (Carica papaya L.) in Mexico. Four representative strains of soil-derived Rhizopus spp. were analyzed employing molecular, microscopic, and metabolic methods. The ITS phylogenies identified the fungi as Rhizopus microsporus HP499, Rhizopus delemar HP475 and HP479, and Rhizopus homothallicus HP487. We discovered that R. microsporus HP499 and R. delemar HP475 harbor similar endofungal bacterial symbionts that belong to the genus Mycetohabitans (Burkholderia sensu lato) and that none of the four fungi were associated with Narnavirus RmNV-20S and RmNV-23S. Intriguingly, the interaction between R. delemar - Mycetohabitans showed different phenotypes from known R. microsporus - Mycetohabitans symbioses. Elimination of bacteria in R. delemar HP475 did not cause a detrimental effect on fungal growth or asexual reproduction. Moreover, metabolic and molecular analyses confirmed that, unlike symbiotic R. microsporus HP499, R. delemar HP475 does not produce rhizoxin, one of the best-characterized toxins produced by Mycetohabitans spp. The rhizoxin (rhi) biosynthetic gene cluster seems absent in this symbiotic bacterium. Our study highlights that the symbioses between Rhizopus and Mycetohabitans are more diverse than anticipated. Our findings contribute to expanding our understanding of the role bacterial symbionts have in the pathogenicity, biology and evolution of Mucorales.